High-performance liquid chromatographic determination of arbutin in skin-whitening creams and medicinal plant extracts - Thongchai W. (2014)
A high-performance liquid chromatographic method was developed for quantitative analysis of arbutin. The arbutin was separated on an ODS Hypersil® C18 column with a mobile phase of water:methanol:0.1 M hydrochloric acid (89:10:1, v/v/v). The level of arbutin was measured by means of UV detection at 222 nm. The optimum conditions for arbutin quantitative analysis were investigated. The calibration curve was found to be linear up to 1,000 μg/ml-1 of arbutin concentration, and the working calibration curve for arbutin determination over the range 0.5-30.0 μg/ml-1 of arbutin (r2 = 0.9999) was established. The relative standard deviations for intraday and interday were found to be 0.98% and 1.15%, respectively. A detection limit (3σ) and quantitation limit (10σ) of 0.02 μg/ml-1 and 0.2 μg/ml-1, respectively, and a mean percentage recovery of the spiked arbutin of 99.88 ± 1.12% were obtained. The proposed method has been applied to the determination of arbutin in commercial skin-whitening creams (Arbuwhite® cream, Super Whitening® cream, and Shiseido® cream) with average contents of 7.60, 5.30, and 57.90 mg/g-1, respectively. It was also applied to the determination of arbutin in medicinal plant extracts from Betula alnoides Buch. Ham., Clerodendrum petasites S. Moore, Curculigo latifolia Dryand. Var. latifolia, and Hesperetbusa crenulata (Roxb.) Roem, levels of which were found to be 3.50, 1.50, 1.10, and 0.12 μg/g-1, respectively (no article reported in the literature about arbutin analysis). The proposed HPLC method is rapid, simple, and selective for routine analysis.